Elaborately carved temple ceiling - Temples of India Project Team (Jio Institute, 2024)
The elaborately carved temple ceiling features a panel on the right carved with multiple male and female figures. In the centre is a prominent bearded male figure holding a drum. The central portion of the panel is significantly defaced.